2001
DOI: 10.1046/j.1524-475x.2001.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of embryonic stem cells: Genetic and epigenetic methods

Abstract: Embryonic stem cells are derived from the inner cell mass of the pre-implantation blastocyst, and can both self-renew and differentiate into all the cells and tissues of the body. The embryonic stem cell is an unsurpassed starting material to begin to understand a critical, largely inaccessible, period of development, as well as an important source of cells for transplantation and gene therapy. Despite their potential, attempts to obtain specific cell types from embryonic stem cells have been only partially su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 162 publications
0
13
0
Order By: Relevance
“…Cultured ES cells can generate extra-embryonic cell types and derivatives of the three primary germ layers, ectoderm, mesoderm, and endoderm (Dushnik-Levinson and Benvenisty, 1995;Niwa et al, 2000;O'Shea, 2001;Fujikura et al, 2002). We (Chen and Gudas, 1996) have shown that RA induces differentiation into an extraembryonic epithelial cell type called primitive endoderm and causes growth arrest of ES cells in the presence of LIF, thereby overriding the LIF-induced signaling pathways which otherwise maintain selfrenewal of ES cells.…”
mentioning
confidence: 99%
“…Cultured ES cells can generate extra-embryonic cell types and derivatives of the three primary germ layers, ectoderm, mesoderm, and endoderm (Dushnik-Levinson and Benvenisty, 1995;Niwa et al, 2000;O'Shea, 2001;Fujikura et al, 2002). We (Chen and Gudas, 1996) have shown that RA induces differentiation into an extraembryonic epithelial cell type called primitive endoderm and causes growth arrest of ES cells in the presence of LIF, thereby overriding the LIF-induced signaling pathways which otherwise maintain selfrenewal of ES cells.…”
mentioning
confidence: 99%
“…Numerous research .groups are currently involved with improving and modifying the existing basic in vitro differentiation protocols, and the results achieved are encouraging II4, 116,2837. Regarding the protocols based on manipulations of the hESC genome, these provide interesting scientific possibilities 79,142,209,2707 (see also 7947). However, from the clinical perspective, manipulations of this nature raise important ethical and safety concerns.…”
Section: Reviews In the Neurosciencesmentioning
confidence: 99%
“…Furthermore, the differentiation of a homogeneous population of cells has been problematic due to the routine production of multiple cell types using differentiation protocols [85]. For cell transplantation studies to be successful, it will be important to establish robust protocols for the production of pure populations of cells [16, 47, 85, 86].…”
Section: Clinical Considerations For the Transplantation Of Stem Cellmentioning
confidence: 99%